Athens and Macedon : Attic letter-cutters of 300 to 229 B.C - Tracy, Stephen V. (Hellenistic culture and society, 2003)
Little of the historiography of 3rd century Athens survives, and much of what we know about the period has come down to us in inscriptions carved by Attic stonemasons of the time. This text provides an insight into an unsettled and obscure moment in antiquity